Novel Approach to Estimate Osteoarthritis Progression: Use of the Reliable Change Index in the Evaluation of Joint Space Loss. Issue 2 (29th January 2019) - Parsons, Camille M.; Judge, Andrew; Leyland, Kirsten; Bruyère, Olivier; Petit Dop, Florence; Chapurlat, Roland; Reginster, Jean‐Yves; Edwards, Mark H.; Dennison, Elaine M.; Cooper, Cyrus; Inskip, Hazel; ,
Abstract : Objective: Osteoarthritis‐related changes in joint space measurements over time are small and sensitive to measurement error. The Reliable Change Index (RCI) determines whether the magnitude of change observed in an individual can be attributed to true change. This study aimed to examine the RCI as a novel approach to estimating osteoarthritis progression. Methods: Data were from 167 men and 392 women with knee osteoarthritis (diagnosed using the American College of Rheumatology criteria) randomized to the placebo arm of the 3‐year Strontium Ranelate Efficacy in Knee Osteoarthritis trial (SEKOIA) and assessed annually. The RCI was used to determine whether the magnitude of change in joint space width (JSW) on radiographs between study years was likely to be true or due to measurement error. Results: Between consecutive years, 57–69% of participants had an apparent decrease (change <0) in JSW, while 31–43% of participants had annual changes indicating improvement in JSW. The RCI identified JSW decreases in only 6.0% of patients between baseline and year 1, and in 4.5% of patients between the remaining study years. The apparent increases in JSW were almost eliminated between baseline and year 1, and between years 1 and 2 only 1.3% of patients had a significant increase, dropping to 0.9% between years 2 and 3. Conclusion: The RCI provides a method to identify change in JSW, removing many apparent changes that are likely to be due to measurement error. This method appears to be useful for assessing change in JSW from radiographs in clinical and research settings.